Research on application of a new bottom trap technology to catch particles rich in nutrients in a large shallow lake. (15th December 2021) - Zhang, Yihui; Hu, Yuemin; Peng, Zhaoliang; Hu, Weiping; Zhu, Jinge
Abstract: The resuspension and sedimentation of particulate matter and the release of nutrients from sediment are important factors affecting the eutrophication of shallow lakes. The capture and removal of particles rich in nitrogen, phosphorus, and other nutrients at the bottom of lakes is of great significance for improving the management and eutrophication status of lakes. This study investigated the feasibility of applying lake bottom trap technology in seven different locations in Lake Chaohu, which is the fifth largest freshwater lake in China. The results showed that the trap in the western part of Lake Chaohu had the highest sedimentation rate and could capture most of the nutrients. The sedimentation rates were higher in spring and summer than in autumn and winter. The bottom trap effectively collected and preserved chlorophyll a, organic matter, total nitrogen, and total phosphorus. The trap per meter length (15–20 m wide) could catch 20.7–27.6 m 3 of particles rich in nutrients with a water content of 50–70%, organic matter content of 281.9–375.8 kg, total nitrogen content of 24.5–32.6 kg, and total phosphorus content of 10.5–14 kg. The proposed bottom trap had little impact on the benthic organism system of the lake. The bottom trap technology used in this study could solve the problem of nitrogen, phosphorus, and algae accumulation in lakes and reservoirs, broaden the utility of lake hydrodynamics in environmental pollution control, and provide new ideas and strategies for the control and management of cumulative pollution in shallow lakes and reservoirs. Graphical abstract: Image 1 Highlights: Ability of bottom trap technology to capture high-nutrient particles was evaluated. The bottom trap has the advantage of low impact on benthic organisms. It provides new strategies for the control of cumulative nutrient in shallow lakes. It broadens the utility of lake hydrodynamics in water environmental improvement.